2017
DOI: 10.1152/ajpendo.00084.2017
|View full text |Cite
|
Sign up to set email alerts
|

Factors regulating subcutaneous adipose tissue storage, fibrosis, and inflammation may underlie low fatty acid mobilization in insulin-sensitive obese adults

Abstract: Although the rate of fatty acid release from adipose tissue into the systemic circulation is very high in most obese adults, some obese adults maintain relatively low rates of fatty acid release, which helps protect them against the development of systemic insulin resistance. The primary aim of this study was to identify factors in adipose tissue that may underlie low vs. high rates of fatty acid mobilization in a relatively homogeneous cohort of obese adults. We measured systemic fatty acid rate of appearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
3
9
0
Order By: Relevance
“…There was an accumulation of proteins found to be related to or involved in fibrosis-associated processes in obob mice, compared to the controls. This is consistent with the excess accumulation of adipose tissue extra cellular matrix (ECM) components and IR in obesity [28], and to a recent observation of the ECM organization and assembly markers that were increased in obese humans with a high serum FFA mobilization from adipose tissue [29].…”
Section: Discussionsupporting
confidence: 84%
“…There was an accumulation of proteins found to be related to or involved in fibrosis-associated processes in obob mice, compared to the controls. This is consistent with the excess accumulation of adipose tissue extra cellular matrix (ECM) components and IR in obesity [28], and to a recent observation of the ECM organization and assembly markers that were increased in obese humans with a high serum FFA mobilization from adipose tissue [29].…”
Section: Discussionsupporting
confidence: 84%
“…This study was part of a larger investigation of the relationship between FA mobilization and insulin resistance in obese adults. Some of the methods for this study have been reported elsewhere (Van Pelt et al, 2017) but are briefly repeated here for convenience.…”
Section: Ethical Approvalmentioning
confidence: 99%
“…Participants were studied after an overnight fast during the follicular phase of their menstrual cycle. We collected a baseline blood sample and a subcutaneous abdominal adipose tissue sample, under local anaesthetic (Van Pelt et al, 2017). The rate of appearance of FA in the systemic circulation (FA Ra) was assessed using 13 C-palmitate isotope dilution as detailed elsewhere (Van Pelt et al, 2017).…”
Section: Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations